Extreme cyclone events in the Arctic: Wintertime variability and trends. (23rd August 2017) - Rinke, A; Maturilli, M; Graham, R M; Matthes, H; Handorf, D; Cohen, L; Hudson, S R; Moore, J C
Abstract: Typically 20–40 extreme cyclone events (sometimes called 'weather bombs') occur in the Arctic North Atlantic per winter season, with an increasing trend of 6 events/decade over 1979–2015, according to 6 hourly station data from Ny-Ålesund. This increased frequency of extreme cyclones is consistent with observed significant winter warming, indicating that the meridional heat and moisture transport they bring is a factor in rising temperatures in the region. The winter trend in extreme cyclones is dominated by a positive monthly trend of about 3–4 events/decade in November–December, due mainly to an increasing persistence of extreme cyclone events. A negative trend in January opposes this, while there is no significant trend in February. We relate the regional patterns of the trend in extreme cyclones to anomalously low sea-ice conditions in recent years, together with associated large-scale atmospheric circulation changes such as 'blockinglike' circulation patterns (e.g. Scandinavian blocking in December and Ural blocking during January–February).